2015
DOI: 10.1103/physrevapplied.4.064010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrode Roughness on Electroforming inHfO2and Defect-Induced Moderation of Electric-Field Enhancement

Abstract: The roughness of Pt electrodes is shown to have a direct impact on the electroforming characteristics of Pt=Ti=HfO 2 =Pt device structures. Specifically, an increase in roughness leads to a reduction in the electroforming voltage of HfO 2 , an increase in the failure rate of devices, and a corresponding reduction in resistive switching reliability. A finite-element model is used to investigate the significance of local electricfield enhancement on the breakdown process. This simulation shows that high-aspect-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…A finite element method (FEM) was used to map the potential distribution in the device using the COMSOL Multiphysics 5.2 program. We adapted the numerical model approach from previously reported works on RS 18,33 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A finite element method (FEM) was used to map the potential distribution in the device using the COMSOL Multiphysics 5.2 program. We adapted the numerical model approach from previously reported works on RS 18,33 .…”
Section: Methodsmentioning
confidence: 99%
“…The morphology of the surface and interface can alter the operational characteristics of microelectronic devices significantly. For example, it has been reported that a rough surface morphology can increase the leakage current 17 , reduce breakdown voltage 18 , and reduce the yield in thin film oxide capacitance 19 . However, there are conflicting reports on the effect of surface morphology of the top and bottom electrodes on ReRAM performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified model showing the physical mechanisms behind a progressive reduction in SET as well as the surface roughness of the BE is illustrated in Figures 7(a)-7(b). During formation of single/multiple conductive filaments, not only the current compliance but also the surface roughness at the metal/oxide interfaces are important, since this would lead to local electric-field enhancements and then early breakdown [20,21]. Figure 6(b), the power needed to promote continuous resistive switching of that MIM structure is reduced, while the memory window ( ON / OFF ratios) increases.…”
Section: Resultsmentioning
confidence: 93%
“…This behavior could be attributed to the surface roughness of the OCs (Fig. 2g), which may lead to localized electric-field enhancements leading to an early breakdown 51–53 . A study of the effects of the electrodeposition parameters on the surface roughness 54 , i.e.…”
Section: Resultsmentioning
confidence: 99%